Laser assisted zona hatching does not lead to immediate impairment in human embryo quality and metabolism. (1st November 2016) - Uppangala, Shubhashree; D'Souza, Fiona; Pudakalakatti, Shivanand; Atreya, Hanudatta S.; Raval, Keyur; Kalthur, Guruprasad; Adiga, Satish Kumar
ABSTRACT: Laser assisted zona hatching (LAH) is a routinely used therapeutic intervention in assisted reproductive technology for patients with poor prognosis. However, results are not conclusive in demonstrating the benefits of zona hatching in improving the pregnancy rate. Recent observations on LAH induced genetic instability in animal embryos prompted us to look into the effects of laser assisted zona hatching on the human preimplantation embryo quality and metabolic uptake using high resolution nuclear magnetic resonance (NMR) technology. This experimental prospective study included fifty embryos from twenty-five patients undergoing intra cytoplasmic sperm injection. Embryo quality assessment followed by profiling of spent media for the non-invasive evaluation of metabolites was performed using NMR spectroscopy 24 hours after laser treatment and compared with that of non-treated sibling embryos. Both cell number and embryo quality on day 3 of development did not vary significantly between the two groups at 24 hours post laser treatment interval. Time lapse monitoring of the embryos for 24 hours did not reveal blastomere fragmentation adjacent to the point of laser treatment. Similarly, principal component analysis of metabolites did not demonstrate any variation across the groups. These results suggest that laser assisted zona hatching does not affect human preimplantation embryo morphology and metabolism at least until 24 hours post laser assisted zona hatching. However, studies are required to elucidate laser induced metabolic and developmental changes at extended time periods. Abbreviations : AH: assisted hatching; ART: assisted reproductive technology; DNA: deoxy-ribo nucleic acid; LAH: laser assisted hatching; MHz: megahertz; NMR: nuclear magnetic resonance; PCA: principal component analysis; PGD: preimplantation genetic diagnosis; TLM: time lapse monitoring